Foreign Experience in Establishing Carbon Prices for Energy Consumption - Choriyev Fazliddin ISHKUVATOVICH (International Journal of Environmental, Sustainability, and Social Science, 2025)
This article studies foreign experience in setting carbon prices for energy consumption. The significance and results of the measures taken by foreign scientists and governments are studied. It also aims to conclude the impact of setting these carbon prices on the economy and their implementation in developing countries through the study of supporting the green economy. The methodology used for the study included interpretation methods. Also, within the framework of the topic, the views of scientists and the work carried out by international financial institutions on changes in world trends and measures taken and goals were analyzed, and relevant conclusions and proposals were presented. In this, induction, deduction, and comparative analysis were used. It also highlights the advantages and disadvantages of this practice, and its importance by studying its implementation methods. The level of government participation in the implementation of pricing policy and scientific conclusions is drawn based on the data studied. The process of supporting the "Green Economy" around the world is developing rapidly. Also, subsidizing electricity with the aim of reducing poverty may not always yield positive results.